Comparison of orthopedic trauma patterns in geriatric patients during COVID-19 pandemic led lockdown and non-lockdown periods - Singh, Arpit; Roy, Shubhajeet; Singh, Vaishali; Mohan, Ravindra; Shantanu, Kumar; Agarwal, Abhishek; Kushwaha , Narendra Singh; Kumar, Abhishek; Srivastava, Devesh; Gupta, Shikhar S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Lockdown had hindered persons’ ability to engage in regular physical activity. Our study analysed bone trauma patients who visited the orthopedic department based on the mode of injury, kind of extremity involved, and the bone implicated. Methods: This was a retrospective cross-sectional study of patients visiting the orthopedic surgery department of a North Indian tertiary health care centre. Patient data was recorded from the case sheets. Results: A total of 792 patients’ data was collected, out of which 250 patients were those of during lockdown, and 542 patients were of non-lockdown phase. During the lockdown phase, the patients who have undergone RTA were 37 (14.8%), those admitted for domestic trauma were 128 (51.2%), and those for miscellaneous causes were 85 (34%). During the non-lockdown phase, RTA were 145 (26.739%), domestic were 318 (58.608%) and miscellaneous were 79 (14.652%). During lockdown, the site of injury was upper limb in 59 patients, lower limb in 154 patients, vertebrae in 37 patients. In the non-lockdown phase, the upper limb was injured in 95 patients, lower limb in 377 patients, vertebrae in 52 patients and hip bone in 17 patients. Femur was the most affected bone. Conclusions: There was a decrease in the number of instances during the lockdown. During both the periods, the majority of geriatric patients were from rural areas. Domestic trauma cases were most prevalent in the older age range, and the most common extremity implicated appeared to be the lower limb, with the femur being the most involved bone in both stages.